ASSESSMENT OF SPECIES DIVERSITY AND GERMPLASM CONSERVATION OF RARE FRUIT PLANTS IN THE TAMAN CANDRA WILWATIKTA COLLECTION GARDEN, PANDAAN, INDONESIA - Achmadi Susilo; Dwi Retna Suryaningsih; M. Thohiron; Faez M. Hassan; Achmad Wicaksono (International Journal of Multidisciplinary Research and Literature, 2026)
The conservation of rare fruit plant germplasm over the coming decade will continue to rely primarily on conventional approaches, namely ex situ and in situ conservation, to preserve seeds or entire plants. Fruit germplasm resources need to be collected and characterized for conservation purposes as well as for use in plant breeding programs. This study aimed to evaluate the existing condition of the Rare Fruit Plant Collection Garden, including fruit species diversity and population size, utilization levels, development status, management constraints, and potential solutions as part of an ex situ conservation effort. The study employed a reassessment approach by re-examining the results of previous species identification. The observed variables included the current diversity of fruit plant species, population size of all species, the level of collection garden utilization, and management constraints. Secondary data were also collected as necessary to complement the analysis. Field observations and assessments were conducted from November to December 2025. The results showed that, at the time of evaluation, the Collection Garden still contained 112 fruit species with a total population of 283 trees. Of the 128 fruit species recorded, 83 species (64.84%) had been cultivated, while the remaining 45 species (35.16%) had not yet been developed. Based on growth habit, 112 species (87.50%) were classified as trees, 8 species (6.25%) as herbaceous tree-like plants, and 3 species (2.34%) as shrubs. Currently, the Collection Garden is utilized for harvesting fruit products, as a practical learning facility for students of the Faculty of Agriculture, as a source of plant materials for research and scientific development, and as an agro-tourism destination for visitors staying at Taman Candra Wilwatikta. Several constraints were identified in the management of the Collection Garden, including vandalism and theft by local residents, inadequate supervision by garden personnel, difficulties in water distribution, the absence of greenhouse facilities, the lack of rejuvenation and characterization programs, and challenges related to routine plant maintenance.